2003
DOI: 10.1021/bi0269916
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Prion Structural Changes Revealed by High Pressure

Abstract: At high temperature, recombinant hamster prion protein (SHaPrP(90-231)) undergoes aggregation and changes from a predominantly alpha-helical to beta-sheet conformation. We then applied high pressure (200 MPa) to the beta-sheet-rich conformation. The aggregation was reversed, and the original tertiary and secondary structures were recovered at ambient pressure, after pressure release. The application of a pressure of 200 MPa thus allowed studying the heat-induced equilibrium refolding in the absence of protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 53 publications
6
71
1
1
Order By: Relevance
“…About 30% of amyloid fibrils became dissociated into soluble species, whereas the remaining fibrils stayed in fibrillar form but lost some of the amyloid-specific features. High pressure refolding of temperature-induced ␤-sheetrich aggregates of a mammalian prion protein has been previously reported (55,56). However, to our knowledge, none of the ␤-sheet-rich misfolded conformers was described to display amyloid fibril structure.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…About 30% of amyloid fibrils became dissociated into soluble species, whereas the remaining fibrils stayed in fibrillar form but lost some of the amyloid-specific features. High pressure refolding of temperature-induced ␤-sheetrich aggregates of a mammalian prion protein has been previously reported (55,56). However, to our knowledge, none of the ␤-sheet-rich misfolded conformers was described to display amyloid fibril structure.…”
Section: Discussionmentioning
confidence: 81%
“…We, thus, suggest that pressurized fibrils should be considered as a new alternative conformation that can be reached by a protein under certain physicochemical conditions. Indeed, previous insight into unexplored conformational states of the recombinant cellular PrP isoform was obtained using high pressure (55,56,(62)(63)(64)(65)(66). The results revealed that these PrP states are distinguished by their volumetric properties (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…This apparent discrepancy with the present study could be explained if the PK-resistant 35 SPrP products represent folding intermediates (and not bona fide PrP Sc ) that are capable of reversing to PK-sensitive 35 SPrP molecules. Other reports that analyzed recombinant prion protein aggregation into ␤-sheet-rich structures were able to demonstrate a reversion to the original ␣-helical structure under certain conditions (29,30). These studies suggest that there are folding intermediates in the transition from PrP C to PrP Sc .…”
Section: Fig 4 Prpmentioning
confidence: 74%
“…This appears to be caused by an aberrant conformational change of the cellular PrP, leading to its deposition in the form of amyloid fibrils. Recently, we have shown that using high-pressure perturbation, recombinant PrP can be converted to different novel misfolded conformers (13)(14)(15). By a judicious choice of pressure, temperature, pH, and incubation time, it is possible to attain several distinct PrP structures.…”
Section: Pressure Effects On Tertiary Structure: the Case Of Prion Prmentioning
confidence: 99%